Online Discussion Application and Multimedia Use on Elearning in Curriculum Study of Junior and Senior High School in Civic Education Program - Fatihah, Husnul (Jurusan Ilmu Sosial Politik Fakultas Ilmu Sosial Universitas Negeri Padang, 2018)
This study aims to develop elearning learning based on supplemental elearning mapping in the curriculum course of SMP and SMA in PPKn III semester study program on MoDELss website (Moodel Elearning for Sriwijaya Student). This research uses development method by Rowntree. There are three phases in this study: the planning stage, the development stage, and the evaluation stage Material validity test, multimedia is done by Sriwijaya University Quality Assurance Unit which the result is declared good with number 84. The development is done by displaying multimedia in the form of best video made by student of semester III of previous academic year and conducted online discussion from multimedia display. The results showed an increase in student learning motivation, shown by students who actively discuss online and actively make learning videos based on the results of group discussions as well as actively viewing or downloading learning videos. Keywords: character education, student coaching, SMA Adabiah high school Padang ABSTRAK Penelitian ini bertujuan untuk mengembangkan pembelajaran elearning berdasarkan mapping suplemental elearning dalam mata kuliah Telaah Kurikulum SMP dan SMA Program Studi PPKn semester III pada website MoDELss (Moodel Elearning for Sriwijaya Student). Penelitian ini menggunakan metode pengembangan Rowntree. Ada tiga fase dalam penelitian ini: tahap perencanaan, tahap pengembangan, dan tahap evaluasi. Uji validitas materi, multimedia dilakukan oleh Unit Penjamin Mutu Universitas Sriwijaya yang hasilnya dinyatakan baik dengan angka 84. Pengembangan dilakukan dengan menampilkan multimedia berupa video terbaik yang dibuat oleh mahasiswa semester III tahun ajaran sebelumnya dan dilaksanakan diskusi online dari tampilan multimedia tersebut. Hasil pengamatan menunjukkan peningkatan dalam motivasi belajar siswa, ditunjukkan oleh mahasiswa yang aktif berdiskusi online dan aktif membuat video pembelajaran berdasarkan hasil diskusi kelompoknya serta aktif melihat atau mendownload video pembelajaran. Kata kunci: pendidikan karakter, pembinaan kesiswaan, SMA Adabiah Padang